PENERAPAN PROGRAM PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) (STUDI TENTANG MODAL SOSIAL PADA PELAKSANAAN BIDANG KESEHATAN,PENDIDIKAN DAN KETERAMPILAN PROGRAM PKK KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU) - Asriwandari, Hesti; Al’amin, Afriliya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Implement program Family Welfare Empowerment (PKK) study of social capital in the implementation of health and education skills program PKK Kelurahan Simpang Baru Kecamatan Tampan of the city of Pekanbaru. PKK is a movement of people who have been actively involved as a partner of the government in the implementation of community development programs. PKK have an essential role that is driving an empowering women to actively participate in development and as an institution with the primary mission of the family realize prosperous, advanced and independent with a growing number of job performance, has won the recognition of its existence amongst the people. With regard essentially have and implement 10 programs PKK institutionalized and accepted by society because in accordance with the demands of life and livelihood in improving public welfare and unseen seen from the social capital of the execution of health, education and skills. The aim of the study is to examine social capital as measured by indicators of norms, networks and trust and know the benefits of the program PKK health and education skills Simpang Baru PKK. The method in this research using descriptive quantitative research methods, probability sampling design, using simple random sampling technique, sample is 96 to the formula slovin, respondents who are part of all members of the PKK. Researchers in data collection using observation, a questionnaire (questionnaire) and documentation. These results indicate that the PKK program implementation in health, education and skills high social capital as measured by indicators of norms, networks and trust. The norms make the program run properly. The program runs well in a network. A network has been formed to create and build trust. This continues to occur continuously and repeatedly so that the PKK programs in health, education and skills is going well. The perceived benefits of members is the result of applying the PKK programs in health, education and skills. The perceived benefits are closely related to improving the quality of health and education quality and skills of PKK members in accordance with the government's program of human resource empowerment and improving social welfare. Keywords: PKK, PKK Program Implementation, Social Capital, Benefits